Psychosocial impact of pediatric living‐donor kidney and liver transplantation on recipients, donors, and the family: a systematic review. (21st November 2014) - Thys, Kristof; Schwering, Karl‐Leo; Siebelink, Marion; Dobbels, Fabienne; Borry, Pascal; Schotsmans, Paul; Aujoulat, Isabelle; the ELPAT Pediatric Organ Donation; Transplantation Working Group
Summary Living‐donor kidney and liver transplantation intend to improve pediatric recipients' psychosocial well‐being, but psychosocial impact in recipients strongly depends upon the impact on the donor and the quality of family relations. We systematically reviewed quantitative and qualitative studies addressing the psychosocial impact of pediatric living‐donor kidney and liver transplantation in recipients, donors, and the family. In accordance with the PRISMA guidelines, we systematically searched the databases Medline, Web of Knowledge, Cinahl, Embase, ERIC, and Google Scholar. We identified 23 studies that satisfied our inclusion criteria. Recipients had improved coping skills and satisfactory peer relationships, but also reported anxiety and depressive symptoms, worried about the future, and had a negative body image. Similarly, donors experienced increased self‐esteem, empowerment, and community awareness, but also complained of postoperative pain and a lack of emotional support. With respect to family impact, transplantation generated a special bond between the donor and the recipient, characterized by gratitude and admiration, but also raised new expectations concerning the recipient's lifestyle. As psychological problems in recipients were sometimes induced by feelings of guilt and indebtedness toward the donor, we recommend more research on how gift exchange dynamics function within donor–recipient relationships, enrolling donors and recipients within the same study.